Assessing Institutional Support From Dietetics Associations Toward Integration of Sustainable Food Concepts in Dietetics Practice - Callaghan, Edith G.; Powell, Rachael; Carlsson, Liesel (Frontiers in Sustainable Food Systems, 2022)
The degrees to which diets are consistent with food system sustainability, are the result of influences across scales of social interaction. This study considers the importance and limitations of institutional influence over integration of sustainable food systems ideas and concepts in dietetics practice. Working with the International Confederation of Dietetics Associations (ICDA) and their Member Country Associations our objectives are to (a) understand ways by which ICDA could contribute to global sustainable food systems, (b) develop a method for assessing ICDA's contribution to sustainable food systems and (c) test initial data collection options for this assessment. Assessment of institutional support for sustainable food system integration to practice was conducted by examining usage data (from Google Analytics) of the ICDA sponsored online sustainable food system Toolkit, and website content analysis. Study results establish baseline data and indicate initially modest support for backing integration of sustainable food system concepts within the dietetics profession.